Intégrer la territorialité pour une économie de la fonctionnalité plus soutenable - Philippe Roman; Coralie Muylaert; Coline Ruwet; Géraldine Thiry; Kevin Maréchal (Développement Durable et Territoires)
Product-service systems (PSS) are often presented as a new model which would be conducive to sustainable development. In most English-speaking work on PSS, the environmental dimension is at times put to the fore, or even considered as inherent to the model, but the issue of the territorial insertion of such activities is not addressed, or just in passing. Numerous reasons justify thinking that implementing PSS activities without considering their territorial embeddedness may end up with outcomes short of their full sustainability potential. We therefore believe it is important to explicitly question the territoriality of PSS initiatives. In the present article, we perform a literature review on the PSS-territory nexus and we propose a discussion aiming at shedding light on the relevance of integrating a territorial reflection to the scientific work on PSS.